On the generators of the kernels of hyperbolic group presentations - Chaynikov, V. (Algebra and Discrete Mathematics, 2011)
In this paper we prove that if R is a (not necessarily finite) set of words satisfying certain small cancellation condition in a hyperbolic group G then the normal closure of R is free. This result was first presented (for finite set R) by T. Delzant [Delz] but the proof seems to require some additional argument. New applications of this theorem are provided.